The Importance of The Advanced Technology Sector in The Structure of National Economies and Economic Growth - Małgorzata JUCHNIEWICZ; Magdalena ŁADA (Communications of International Proceedings, 2022)
So far, systematized information on the high technology sector has left a research gap regarding its importance in the structure of national economies and its impact on economic growth. Therefore, the question arises how important is the advanced technology sector in the European Union countries and does it have a significant impact on economic growth? It was a premise for undertaking research enabling the assessment of the competitive potential of the sector in the structure of national economies and the degree of connection with economic growth. The starting point was the definition of economic growth and the high technology sector. Then, on the basis of selected indicators, the importance of the high-tech sector was examined in comparison to all sectors operating in the European Union countries. For this purpose, the following were calculated: share of the number of enterprises, share of the number of employees, share of the production value of the high technology sector. It was also assessed whether there is a relationship between the above-mentioned indicators and GDP per capita. As a result of the research, the countries in which the advanced technology sector plays an important role were indicated, and the degree of dependence between individual indicators and GDP per capita was indicated.
Keywords: high technology sector; economic growth; national economy; competitiveness; GDP